O riso e suas implicações na obra Os dous ou o Inglês maquinista, de Martins Pena - Valdrighi, Rachel Sant'ana (2018)
This work intends to study artifacts of textual construction in Martins Pena's play Os Dous ou o Inglês Maquinista, written probably in 1840 and published in 1843. The goal was to analyze the comic devices used by the playwright, with the specific objectives of not only to investigate which devices are, but also how they occur, what kind of laughter they may cause, and how they serve as a herald of comedy for the future staging. To that end, one wonders: What are the comic devices present in the play Os Dous ou o Inglês Maquinista? Can these be understood as indicators of comedy for a future staging? How do they work and what kind of laughter do they cause? The questioning was guided by the following hypotheses: the play Os Dous ou o Inglês Maquinista uses different devices of comedy, generators of different types of laughter that imply social and aesthetic tension; the comedy operationalized in the textual composition foresees effects that are intended in the staging, in other words, in the play as a spectacle. As a theoretic foundation, it relies on scholars of Comedy, such as Bergson, Propp, among others. Building a work within the traditional structures of comedy, Martins Pena use several elements that generate laughter, from satire and caricature, such as exaggeration, nonsense and misunderstandings